New vertebrate remains from the Batoví Member (Late Jurassic-?Early Cretaceous) of the Tacuarembó Formation (Uruguay) and the southernmost occurrence of mawsoniid coelacanths - Soto, M. (2010)
The Batoví Member of the Tacuarembó Formation comprises fossiliferous sandstones and pelites of mainly fluviolacustrine origin, which have yielded a fossil assemblage of Late Jurassic-?Early Cretaceous age. Vertebrates known from the Los Rosanos locality include ?semionotiform bones and scales, dipnoan tooth-plates (Ceratodus africanus Haug), a rostrum of a pholidosaurid mesoeucrocodylian (Meridiosaurus vallisparadisi Mones), and teeth of indeterminate crocodyliforms and theropod dinosaurs. Herein we describe several coelacanth bones (including an operculum, a postparietal, a dentary, and a pterygoid), the ornamentation, morphology and size of which allow us to refer them to the Mawsoniidae, and probably to Mawsonia, being the southernmost record of the genus. Mawsonia, the largest coelacanth, was restricted to non-marine environments of the Tithonian-Cenomanian of Brazil and Africa. The genus has been recently reviewed, only two species being currently recognized. Other mawsoniids from Western Gondwana include Axelrodichthys, Lualabaea and the recently described Parnaibaia. The Uruguayan record is one of the oldest occurrences of the family. Coelacanths are regarded as possible prey of the hybodontid Priohybodus. Other new remains from Los Rosanos include a large theropod tooth (crown height = 56mm) and a crocodyliform skull roof fragment. The tooth, albeit fragmentary, can be referred either to the Ceratosauridae or the Carcharodontosauridae (both taxa being already recorded in the Batoví Member). The skull fragment shows sutured frontals, which indicates it belongs to the Mesoeucrocodylia. All these remains provide valuable information about the fossil assemblages of the Tacuarembó Formation, including the largest fishes and theropods ever recorded in this unit.